A Comparison of Psychosocial Outcomes in Elderly Alzheimer’s Caregivers and Non-Caregivers - Mausbach, Brent T (2013)
OBJECTIVES: To conduct ananalysis of the stress, coping, and mood consequences of Alzheimer’s caregiving. DESIGN: Cross-sectional. SETTING: Community-based study. PARTICIPANTS: Sample included 125 Alzheimer’s caregivers and 60 demographically similar older adults with non-demented spouses (i.e., non-caregivers). MEASUREMENTS: We compared caregivers and non-caregivers on stress, coping, and mood outcomes. We also examined anti-depressant use within the caregiver sample. An emphasis was placed upon effect size differences, including Cohen’s d as well as more clinically meaningful effect sizes. RESULTS: Caregivers were significantly more likely to endorse depressive symptoms and to meet clinically significant cutoff for depression (40% for caregivers; 5% for non-caregivers). Approximately 25% of caregivers reported taking anti-depressant medication, although 69% of these continued to experience significant symptoms of depression. Caregivers also utilized fewer positive coping and greater negative coping strategies relative to non-caregivers. CONCLUSIONS: The number of caregivers will increase dramatically over the next two decades, and caregivers will likely seek care from primary care providers. We provide an overview of the psychological issues facing caregivers so that effective screening and treatment may be recommended.